MENUMBUHKAN SIKAP DISIPLIN MELALUI PEMBUATAN ATURAN KELAS DENGAN STRATEGI PENGELOLAAN KELAS YANG EFEKTIF - Firsly Sekarrini; Yunita Andriyani; Tin Rustini (STKIP Subang, 2022)
In this research article, the author will focus on discipline first and then continue to explain why it is important to have discipline and this can be achieved by having classroom rules and effective classroom management. The term